Occurrence and diversity of basidiomycetous endophytes from the oil palm, Elaeis guineensis in Thailand - Pinruan U. (2014)
Fungal endophytes associated with the oil palm, Elaeis guineensis, at an oil palm plantation in Trang Province, Thailand were investigated. Two samplings at the same site yielded 162 and 178 morphotypes. The overall colonization rate was 81 and 87%, respectively, with non-sporulating species being most common. Twenty strains were identified as basidiomycetes using morphological characteristics and confirmed at the molecular level using ribosomal DNA LSU and ITS sequence data. Species included Fomitopsis cf. meliae, F. cf. ostreiformis, F. cf. pinicola, Perenniporia sp., Pycnoporus sanguineus, Trametes lactinea, and Schizophyllum commune. Leaves supported the greatest number of basidiomycetous taxa (11 strains) with five and four taxa from petioles and rachides, respectively. Twelve taxa produced poroid basidiomes in PDA culture, while the remainder had clamp-connections. Basidiomycetes occurring as saprobes on oil palm were also recorded and compared with those present as endophytes. © Kevin D. Hyde 2010.